ANOPHELES ANOPHELES GABALDONI N SP DEL ESTADO DE TABASCO MEXICO DIPT CULICIDAE - VARGAS (My University, 1940)
A new species of anopheline mosquito, A gabaldoni, is described from Tabasco, Mexico, and placed in the subgenus Anopheles, group Arribalzaga A taxonomic grouping of the spp, subspp and vars of American Anopheles is included
REV MEX MED
Keywords: ANOPHELES, GABALDONI, ESTADO, MEXICO; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA EXPERIMENTAL